Patogenitas cendawan entomopatogen Nomuraea rileyi (Farl.) Sams. terhadap hama Spodoptera exigua Hübner (Lepidoptera: Noctuidae) - Trizelia Trizelia (Perhimpunan Entomologi Indonesia, 2008)
The purpose of this research is to study the pathogenicity of Nomuraea rileyi (Farl.) Sams. to eggs and larvae of Spodoptera exigua Hübner (Lepidoptera: Noctuidae).The fungi were isolated from insect cadaver of S. exigua. Egg clusters and several instar larvae with different conidial concentrations (106 – 109 conidia/ml) were used in the experiment. The results of experiment showed that there was no effect of all concentrations of fungi on egg mortality. Mortality of S. exigua larvae was dependent on the instar and conidial concentration. Generally with increasing conidial concentrations, the mortality were also increasing.